Synthesis of Dibenzo[a,e]cyclooctene-5,11(6H,12H)-diones via the Elusive Benzocyclobutenone Anion - Huang, Yingchao; Chen, Jun; Liu, Yu; Lu, Ping (Synthesis, 2021)
We reported here a facile synthesis of dibenzo[a,e]cyclooctene-5,11(6H,12H)-diones via dimerization of benzocyclobutenones in the presence of simple base via the elusive benzocyclobutenone anion. The temperature effect played a crucial role in the dimerization reaction. Further synthesis of 5,11-disubstituted dibenzo[a,e]cyclooctenes (dibenzo[a,e][8]annulenes) from dibenzo[a,e]cyclooctene-5,11(6H,12H)-diones was also explored.
Keywords: benzocyclobutenone; dibenzo[a,e]cyclooctene-5,11-dione; dibenzo[a,e][8]annulene; carbon–carbon cleavage; dimerization; carbanions